A Simplified Analysis of an Electrical Network with Resistive and/or Reactive Elements (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Typically star-delta transformation is adopted in determining the equivalent impedance between two terminals of an electrical network [2]. Shown relevantly in [1] is a simplified approach, less time-consuming to determine the equivalent resistance between two terminals of an electrical circuit made of resistive elements (of equal values) and, hence the resultant currents in the ciurcuit are determined. This concept is extended and generalized in this study to a class of networks with unequal resistances and/or reactances to determine the equivalent impedance between two nodes. This generalized approach is more comprehensive and universal in analyzing electrical network with complex impedances (regardless of their values). It is applicable to both contexts of circuits with pure resistive elements (as in d.c. analysis) as well as with complex impedances encountered in a.c. analysis.